Stochastic finite element analysis of transient heat transfer in composite materials with interface defects (Archives of Mechanics - Test, 1999)
The paper presented is devoted to the application of the probabilistic computational analysis based on the stochastic finite element methods in the transient heat transfer problems; the field of application of the method introduced is the mechanics of composite materials. The composite materials considered have randomly defined thermal characteristics and, moreover, the interface discontinuities appearing between constituents have a probabilistic character. The influence of all these parameters on the first two probabilistic moments of temperature are verified on the example of a two-component layered composite with an interphase between the constituents.